A conception of moral sensitivity and everyday consumption practices: insights from the moralizing discourses of pet owners. (22nd November 2012) - McEachern, Morven G.; Cheetham, Fiona
Abstract The marketing discipline is somewhat under‐theorized regarding the moral meanings that both shape and are shaped by the everyday consumption practices of consumers. Therefore, using the context of pet ownership, this paper aims to develop a conceptual understanding of the moral aspects of consumption by examining the social construction of morality in consumers' day‐to‐day lives. Using phenomenological interviews and autodriving techniques, the study identifies a number of underlying polemics, linked to the ontology of animals as pets, strands of which weave through participants' moralizing discourses. The study draws attention to the nuances and contradictory processes within which the moral meanings allied to pet ownership and the pet marketplace are constituted and enacted within consumers' day‐to‐day lives. The paper concludes with a discussion on the value of adopting a sociological perspective of consumption morality and its implications for future studies of consumption.